ANALISA PERBANDINGAN KUAT TEKAN BETON PASIR QUARRY MAMUYA TOBELO DENGAN PASIR QUARRY MALANU KOTA SORONG - Wennie Mandela; Stefany Margareta (Politeknik Negeri Jakarta, 2022)
Some of the sand quarry in Sorong City is used by the community in construction work, one of which is the Malanu sand quarry to build houses and shops. Structural work that requires concrete quality above f'c25 MPa using sand from outside the city of Sorong such as from Mamuya Tobelo, of course requires a large amount of cost and longer mobilization time. The purpose of the study was to determine the comparison of the compressive strength of the concrete produced using Tobelo Quarry sand and Malanu Quarry sand and to determine the characteristics of the two types of sand. The research method is an experimental research conducted in a laboratory. The results of the examination of the characteristics of the fine aggregate material of Malanu sand have a mud content value of 7.60%, including coarse sand (gradation 1), a surface dry density value of 2.88 and a water absorption value of 2.15%. The fine aggregate of Tobelo sand has a mud content value of 3.80%, including fine sand (gradation 4), a surface dry density value of 2.62 and a water absorption value of 1.69%. The average compressive strength value of the concrete cylinder uses Malanu sand, the age of 7 days is 10.95MPa, the age of 14 days is 15.10 MPa and the age of 28 days is 17.17MPa. The average compressive strength value of concrete cylinders uses Tobelo sand, the age of 7 days is 13.02MPa, the age of 14 days is 17.17MPa and the age of 28 days is 20.00 MPa. The compressive strength of the concrete cylinder using Tobelo sand is greater than the compressive strength of the Malanu sand concrete cylinder with the difference in the compressive strength value for the age of 7 days 18.90%, age 14 days 13.70% and age 28 days 16.48%.